Development of IoT-Based Physics Teaching Aids for Basic Physics Practicum - Sari Wahyuni Rozi Nasution; Thofik Hidayat; Lia Purnama Sari; Hanifah Nur Nasution; Dwi Aninditya Siregar; Unita Sukma Zuliani Nasution (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an Internet of Things (IoT)-based physics teaching aid for basic physics laboratory practice, focusing on temperature and heat experiments. The research employed a modified Borg & Gall research and development (R&D) model, consisting of six stages: research and information collecting, planning, preliminary product development, preliminary field testing, product revision, and main field testing. The subjects involved were physics education students and expert lecturers as validators. The developed prototype integrated a DS18B20 temperature sensor and ESP8266 microcontroller, enabling real-time data transmission and visualization through a web-based application. Expert validation results showed an average score of 89.38%, categorized as very valid. Student responses reached an average score of 89.92%, indicating the tool was very well received. The feasibility test produced a score of 90.76%, confirming that the product is highly feasible for use in laboratory learning. The findings demonstrate that IoT-based teaching aids can enhance the accuracy of experimental data, increase interactivity, and improve student motivation and conceptual understanding in basic physics. Despite limitations such as WiFi range dependency and the need for sensor calibration, the prototype offers significant potential as a modern instructional medium. In conclusion, the IoT-based teaching aid developed in this study is valid, practical, and feasible, making it a promising innovation for modernizing laboratory practices in higher education and supporting the integration of digital technology into physics education.